Trouble in paradise?: Tech work and its discontents - Valentin Niebler; Helene Thaa; Sandra Sieron; Felix Gnisa (Work Organisation, Labour and Globalisation)
Introducing this special issue, this article gives an overview of recent debates around tech workers in the global economy, with a focus on their subjectivities and labour conflicts. The role of IT professionals has gained new importance through the rise of big tech firms and the diffusion of tech business models across the economy. The more influential role of these new professions has not only created new investment and employment, but also conflict. Economic turbulence, political struggles and industrial disputes have transformed the once-hailed profession into a more contested field of employment. After a general introduction, the article gives an overview of the contributions to this special issue.